A simple method of UV stray light correction for field spectrometers in Ground Validation Sites. Issue 1 (January 2022) - Li, L; Wu, Z; Woolliams, E R; Dai, C; Wang, Y
Abstract: Field spectrometers are widely applied in ground validation sites for remote sensing. However, the control of stray light is one of the most important factors to ensure accurate measurements, since the spectral distribution of target source differs significantly from the laboratory calibration source. Here, a simple UV stray light correction method for continuously distributed wide-spectrum light sources was established by using a set of bandpass filters. This analysis enabled a simple, low-cost method for correcting for the observed straylight.